IMPLEMENTATION OF THE ROLE OF RRI DENPASAR AS INFORMATION DISTRIBUTOR MEDIA IN FACING THE ERA OF MEDIA CONVERGENCE - Ustana Ginanita Utami, Cokorda Istri; Indah Pratiwi, Nuning (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
These community service activities are carried out to become a forum for students to understand the potential possessed by each student so, they will be able to prepare themselves for entering the world of work. Students are demand not just to know theoretical abilities but can also to be more flexible and have a broader insight so that they will be able to solve a problem. In the era of all digital and information disclosure, all institutions are asked to be able to provide information services that are fast, precise, transparent, and responsible to the community. People no longer use conventional media because most of them have accessed the internet. For this reason, there has been a decline in radio consumers. This is certainly a challenge for institutions that carry out their role as information distribution media, especially in conventional radio media. In the step of the advances in information and technology, there has appeared convergence in the media. By integrating conventional mass media with new media, it will be possible to expand the network, audience, and, an interaction that arises.